A helyi pénz számviteli elszámolása - Wickert, Irén; Szarvas-Fekete, Tibor (Acta Scientiarum Socialium, 2013)
Accounting of local currency Today, with the appreciation of local interests the introduction of local money gains ground increasingly. Like money, local currency includes value measuring, circulating (exchanging) and payment functions, but—as it does not carry interests—it cannot fulfil the accumulating and property maintaining functions. As a mean of payment, local money can be compared rather to a voucher than to money in the classical sense, so it can not show up among the liquid assets in the accounting. The legislation of the emission and operation of local currency is only partially solved; there is no specific legislation or central guidance, which determinates the operation of the system in detail. The development of accounting regulations to the related records and settlements will be necessary.